Effects of body mass index on kidney transplant outcomes are significantly modified by patient characteristics. Issue 2 (27th August 2020) - Schold, Jesse D.; Augustine, Joshua J.; Huml, Anne M.; Fatica, Richard; Nurko, Saul; Wee, Alvin; Poggio, Emilio D.
Abstract : Body mass index (BMI) is a known risk factor associated with kidney transplant outcomes and is incorporated for determining transplant candidate eligibility. However, BMI is a coarse health measure and risks associated with BMI may vary by patient characteristics. We evaluated 296 807 adult (age > 17) solitary kidney transplant recipients from the Scientific Registry of Transplant Recipients (2000‐2019). We examined effects of BMI using survival models and tested interactions with recipient characteristics. Overall, BMI demonstrated a "J‐Shaped" risk profile with elevated risks for overall graft loss with low BMI and obesity. However, multivariable models indicated interactions between BMI with recipient age, diagnosis, gender, and race/ethnicity. Low BMI was relatively higher risk for older recipients (>60 years), people with type I diabetes, and males and demonstrated no additional risk among younger (18‐39) and Hispanic recipients. High BMI was associated with elevated risk for Caucasians and attenuated risk among African Americans and people with type II diabetes. Effects of BMI had variable risks for mortality vs graft loss by recipient characteristics in competing risks models. The association of BMI with posttransplant outcomes is highly variable among kidney transplant recipients. Results are important considerations for personalized care and risk stratification. Findings suggest that transplant contraindications should not be based on absolute BMI thresholds but modified based on patient characteristics. Abstract : While body mass index is a well‐established risk factor for inferior kidney transplant outcomes, this report shows that the impact is highly variable, with heterogeneity by recipient age, sex, race/ethnicity, and primary diagnosis.